Fungsi Sosial dan Nilai Budaya Cerita Seharuk dalam Kehidupan Suku Komering di Kabupaten Ogan Komering Ulu Timur Sumatera Selatan - Alviiswari Alviiswari; Halimah; Sumiyadi; Rudi Adi Nugroho (Badan Riset dan Inovasi Nasional (BRIN), 2026)
This study aims to analyze Cerita Seharuk as Komering folklore by examining its social function, cultural value, and narrative context in East OKU Regency. The study uses a qualitative approach with a descriptive-interpretative method. Data were obtained through in-depth interviews with two informants consisting of Komering people and the author of the book Cerita Seharuk, as well as through documentation and observation of performances in cultural activities. Data analysis was carried out using reduction, categorization, and symbolic interpretation techniques. The results of the study show that Cerita Seharuk has a social function as a means of entertainment, moral education, traditional validation, and social control. The cultural values contained therein include obedience to parents, hard work, ingenuity, solidarity, simplicity, and religiosity, which reflect the Komering community's outlook on life. The context of storytelling has undergone a transformation from the domestic sphere of the family to the realm of education and formal cultural activities, demonstrating the dynamic and adaptive nature of folklore in response to the changing times. Theoretically, this research reinforces the study of folklore as a cultural text that not only records social values and functions but also plays a role in maintaining the sustainability of local cultural identity through storytelling practices that continue to undergo transformation. Practically, these findings can form the basis for the development of digital-based media for the preservation of Komering folklore.